Teaching Students To Communicate in English Considerations for Non-Native Speakers of English - Gebhard, Jerry G. ([Washington D.C.] : Distributed by ERIC Clearinghouse, 1999)
The text of a workshop lecture and demonstration focus on the use of instructional materials to enhance the communicative competence of students of English as a Second Language in China. The text of the presentation addresses, in question-and-answer form, seven issues: (1) the varied teaching techniques of teachers in different cultural contexts (in this case, Hungary and Japan); (2) why English should be taught for communication; (3) the nature of communication within and across cultures; (4) the primary goal in teaching students to communicate in English; (5) how teachers can emphasize certain skills to facilitate communication; (6) the kinds of materials useful in teaching communication in English; and (7) how non-native ESL teachers can design communicative language lessons. A lesson is then presented that has workshop participants act as ESL beginners. Materials and classroom procedures are suggested for a lesson on a visit to New York City and a reading lesson. A lesson plan for a workshop activity involving the participants as teachers is also included. Contains 14 references. (MSE)
ERIC Note: Paper presented at a Workshop on EFL Teaching Materials and Pedagogy (Foshan, China, May 10-16, 1999).
Practitioners.
Teachers.
May also be available online. Address as at 14/8/18
Microfiche.
Keywords: Class Activities; Classroom Techniques; Communicative Competence (Languages); English (Second Language); Foreign Countries; Instructional Materials; Intercultural Communication; Lesson Plans; Second Language Instruction; Nonnative Speakers; China; Guides, Classroom -- Teacher; Speeches/Meeting Papers